2019
DOI: 10.1002/app.47890
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of thermoplastic urethanes made from crystalline and amorphous azelate polyols

Abstract: Polyester polyols from renewable resources have gained significant interest in the field of polyurethane chemistry. Two sets of segmented TPUs were prepared from crystalline and amorphous azelate polyols, 4,4′‐methylenebis(phenyl isocyanate), and 1,4‐butanediol as a chain extender at a mole ratio of 1:2:1, respectively. Bio‐1,3‐propanediol (1,3‐PDO) and 1,5‐pentanediol (PTDO) were used to prepare crystalline azelate polyols, while 1,2‐propanediol (1,2‐PDO) and 2,2′‐dimethyl‐1,3‐propanediol (NPG) were used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…254 Both crystalline and amorphous renewable azelate polyols were created to study applications in urethane uses, where the former exhibited mechanical properties suitable for applications requiring heat and abrasion resistance, whereas the latter was suggested for use in coatings and adhesives. 255 When compared to polyols made from shorter diacids such as adipic acid, azelate polyols produced thermoplastic PUs with improved hydrolytic stability. 256 5.4.2.…”
Section: Biobased Diisocyanates and Polyisocyanatesmentioning
confidence: 99%
“…254 Both crystalline and amorphous renewable azelate polyols were created to study applications in urethane uses, where the former exhibited mechanical properties suitable for applications requiring heat and abrasion resistance, whereas the latter was suggested for use in coatings and adhesives. 255 When compared to polyols made from shorter diacids such as adipic acid, azelate polyols produced thermoplastic PUs with improved hydrolytic stability. 256 5.4.2.…”
Section: Biobased Diisocyanates and Polyisocyanatesmentioning
confidence: 99%
“…Variation of mass, flexural strength and viscoelastic response are determined in order to find the changes of the composite [53]. A comparison of TPU/GO and TPU/reduce GO showed that the reduction of GO is not always necessary [54]. The dynamo-mechanical, thermal and mechanical characteristics of long glass fiber reinforced TPU / poly (butylene terephthalate) polyblend have been studied.…”
Section: Compositesmentioning
confidence: 99%
“…Using melt-blending a hybrid made of a shape memory TPU with GO and montmorillonite (MMT) was produced. Thermal analysis showed that GO-MMT enhanced the thermal decomposition of TPU composites [56]. Expandable graphite (EG) is often added to PUs to prevent their flammability.…”
Section: Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicarboxylic acids are one of the main ingredients for making polyester polyols for polyurethane applications and are key building blocks for TPUs. Recently, aliphatic polyesters from bio-derived carboxylic acids have been explored for use in renewable TPUs [ 15 , 16 , 17 ]. Given that we can source azelaic acid from microalgae, the most sustainable photosynthetic biomass, we have focused our attention on developing polyurethanes from this monomer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%